2020
DOI: 10.1002/adfm.202009013
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium Bromides Regulating Solid Electrolyte Interphase Components and Optimizing Solvation Sheath Structure for Suppressing Lithium Dendrite Growth

Abstract: Electrolyte additives play important roles in suppressing lithium dendrite growth and improving the electrochemical performance of long‐life lithium metal batteries (LMBs), however, it is still challenging to design individual additive for adjusting the solid electrolyte interphase (SEI) components and changing lithium ion solvation sheath in the electrolyte at the same time for optimizing electrochemical performance. Herein, alkyl‐triphenyl‐phosphonium bromides (alkyl‐TPPB) are designed as the electrolyte add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 48 publications
0
62
0
Order By: Relevance
“…There was no additional oxidation peak in the HFAcontained electrolyte, which could verify the stability of the electrolyte. [9] Figure S8c and S8d show the first three chargedischarge curves in the blank and HFA-contained electrolytes, respectively. The discharge specific capacity of Li k NCM622 full cell with HFA increases to 169 mAh g À1 , while there is only 160 mAh g À1 in the blank electrolyte.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…There was no additional oxidation peak in the HFAcontained electrolyte, which could verify the stability of the electrolyte. [9] Figure S8c and S8d show the first three chargedischarge curves in the blank and HFA-contained electrolytes, respectively. The discharge specific capacity of Li k NCM622 full cell with HFA increases to 169 mAh g À1 , while there is only 160 mAh g À1 in the blank electrolyte.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Until now, some helpful strategies are reported to inhibit the Li-dendrite growth and stabilize the electrolyte/electrode interface, i.e., electrolyte modification, [8,9] solid-state electrolytes, [10] high-concentration electrolytes and localized highconcentration electrolytes, [11][12][13] ionic liquids, [14,15] structural design of anode materials, [16] special charging methods, [17] etc.…”
mentioning
confidence: 99%
“…[ 32 ] In the fitted spectrum of P, the peak at 137.21 eV ascribed to the PF bond and the peak at 134.02 eV stemming from the LiP bond. [ 33 ] The attached electrolyte was carefully washed off from the lithium foil used for the tests, so the peaks of these bonds should originate from the complex composition of the SEI. To conclude, the simultaneous morphology and composition evolution of the protective layer of CuCl 2 /Li is illustrated in Figure 4i.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] Besides, severe pulverization of the ZnCo 2 O 4 structure with large volume changes usually occurs in host materials during the lithium insertion/release process, which leads to aggregation of particles and accumulation of solid-electrolyte interphase (SEI) layers on the surface and consequently resulting in rapid capacity fading. [15][16][17][18] In previous results, it was found that the stability of ZnCo 2 O 4 could be greatly improved by modifying it with 2D or 3D nanostructures such as coordination polymers, fibrotic metal, and metal-organic frameworks (MOFs). [19,20] Among them, MOF materials are more attractive due to their high surface areas and multiple metal active sites.…”
Section: Porous Mofs-zinc Cobaltite/carbon Composite Nanofibers For High Lithium Storagementioning
confidence: 99%